(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Isotretinoin is frequently used to treat severe acne, although its usage is constrained by systemic, mucocutaneous, and ocular adverse effects. It is frequently regarded as the most effective kind of treatment in such circumstances. The purpose of this study was to assess the population's level of awareness and understanding about the ocular side effects of oral isotretinoin. Methodology: This is a questionnaire-based observational study that was conducted in Saudi Arabia from Aug 2023 – September 2024. The study’s population consisted of Saudi Arabia population in both gender from the age 18 to 60. participants were recruited from people receiving questionnaire. Results: As regard knowledge score about isotretinoin side effects, 42.6% of the sample, demonstrated a high level of knowledge about this medication. However, a sizable proportion of the participants, approximately 33.6%, exhibited a moderate level of knowledge, while 23.9% were classified as having a low level of understanding. Regarding the awareness score (67.8%) exhibits poor awareness. However, 10% exhibits moderate awareness and 22.1% exhibited high awareness. Moreover, (64.4%) were aware that oral isotretinoin can cause dryness of the eyes. Additionally, smaller percentage of participants were aware of other potential ocular side effects, such as itchiness (50.2%), burning sensation (45.7%), blurred vision (33.2%), and eyelid inflammatory conditions (34.9%). Conclusion: While a significant portion of the participants demonstrated a high level of knowledge about the medication itself, there was a concerning lack of awareness about specific ocular side effects, with a majority exhibiting poor awareness overall. The most commonly recognized ocular side effect was dryness of the eyes, while awareness of other potential side effects such as itchiness, burning sensation, and blurred vision varied.